Agile leadership in digital transformation: strengthening resilience, performance, and trust in indonesia’s fintech industry - Gairah Sinulingga; Reina A. Hadikusumo; Syech Idrus; Raden Roro Lia Chairina; Moch Aminudin Hadi (Lentera Negeri, 2026)
This study explores the role of agile leadership in fostering resilience, performance, and trust within Indonesia’s fintech industry during its digital transformation. Using a qualitative research approach through a literature review, the study synthesizes findings from existing research to examine how agile leadership supports fintech organizations in adapting to rapid technological advancements and evolving market demands. The findings indicate that agile leadership enhances organizational resilience by promoting flexibility and adaptability, improves performance through iterative decision-making and continuous learning, and strengthens customer trust by encouraging transparency and continuous improvement. Furthermore, agile leadership enables fintech companies to respond effectively to external disruptions, thereby improving their competitiveness in a dynamic business environment. The study highlights the importance of collaborative, adaptive, and innovative leadership in driving successful digital transformation and provides valuable insights for fintech leaders seeking to sustain organizational performance, resilience, and customer trust in an increasingly competitive industry.